VicPred: A Vibrio cholerae Genotype Prediction Tool - Lee, Imchang; Ha, Sung-Min; Baek, Min-gyung; Kim, Dong Wook; Yi, Hana; Chun, Jongsik (Frontiers in Microbiology, 2021)
Genomic information can be used to predict major pathogenic traits of pathogens without the need for laboratory experimentation. However, no Vibrio cholerae genome-based trait identification tools currently exist. The aim of this study was to develop a web-based prediction tool to identify Vibrio pathogenic traits using publicly available 796 whole-genome sequences of V. cholerae. Using this application, 68 structural O-antigen gene clusters belonging to 49 serogroups of V. cholerae were classified, and the composition of the genes within the O-antigen cluster of each serogroup was identified. The arrangement and location of the CTX prophage, and related elements of the seventh cholera pandemic strains were also revealed. With the versatile tool, named VicPred, we analyzed the assemblage of various SXTs (sulfamethoxazole/trimethoprim resistance element) and major genomic islands (GIs) of V. cholerae, and the increasing trend in drug-resistance revealing high resistance of the V. cholerae strains to certain antibiotics. The pathogenic traits of newly sequenced V. cholerae strains could be analyzed based on these characteristics. The accumulation of further genome data will expedite the establishment of a more precise genome-based pathogenic traits analysis tool.